Comparative Review of Bio-Oil and Liquid Smoke in Terms of Characteristics, Composition, and Applications - Praja, Delphy Yustisia Ayu; Limbong, Fajar Heridoan; Saputro, Erwan Adi (Journal of Renewable Energy and Smart Grid Technology, 2026)
Thermal decomposition process or commonly referred as pyrolysis is one of the methods that can be utilized to obtain several chemical products. Through the pyrolysis process, there are three products produced, each of which can be used; char, tar and bio-oil or liquid smoke. This article will specifically discuss about bio-oil and liquid smoke which are often assumed as the same, but are actually two different things. It is based on the used feedstock, composition of compounds in the product and the utilization of both which are different. To support the writing of the article, a Systematic Literature Review (SLR) method was used to obtain data to analyze and critically compare the differences between bio-oil and liquid smoke. The findings indicate that the used feedstock may affect the quality and characteristics of pyrolysis liquid products. Liquid products obtained from feedstocks contained organic compounds (e.g. biomass) tend to produce high acid and phenol content, called as liquid smoke. While liquid products produced from feedstocks with long carbon chain bonds (e.g. several types of plastics and scrap tires) tend to produce high hydrocarbon compounds called as bio-oil.